A plane wave theory of photoionization using the dipole acceleration form: predictions concerning circular dichroism in photoelectron angular distributions at high energies. (7th October 2020) - Suzuki, Yoshi-Ichi
Abstract: Photoelectron angular distributions for randomly oriented atoms and molecules are characterized by the linear and circular dichroic parameters β and b 1, respectively. In the region where the photoelectron kinetic energy is several 100 eV, the values of b 1 and β are expected to be constants. In this study, we show that β for all hydrogen atom orbitals other than s orbitals approach values between 0 to 0.5 at the high-energy limit in the nonrelativistic dipole approximation and that the values can be obtained by the plane wave approximation using the dipole acceleration form. These limiting values are smaller than the widely accepted values for molecules. We discuss the implications of this result for the circular dichroism in photoelectron angular distributions of linear molecules.